FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA KEUANGAN - Clarissya, Clarissya; Dewi, Sofia Prima (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study was conducted with the aim of obtaining empirical evidence regarding the effect of liquidity, firm size, asset growth, managerial ownership, independent commissioners, and earnings management on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange in 2017 to 2020. Using the purposive method sampling so that the sample used is 40 manufacturing companies that have been selected and the data used for four years is 160 data. This study uses secondary data in the form of financial statements that are processed with Eviews 12 software. The results of this study indicate that liquidity, business size, managerial ownership, and independent commissioners have no negative effect on financial performance, while asset growth has a positive effect on financial performance and earnings management. does not have a positive effect on financial performance.